Cellulite: a review with a focus on subcision - Friedmann DP; Vick GL; Mishra V (Dove Medical Press, 2017)
Daniel P Friedmann,1 Garrett Lane Vick,2 Vineet Mishra3 1Westlake Dermatology Clinical Research Center, Westlake Dermatology & Cosmetic Surgery, Austin, 2Department of Medicine, 3Division of Dermatology and Cutaneous Surgery, The University of Texas Health Science Center at San Antonio, San Antonio, TX, USA Abstract: Cellulite is an alteration in skin topography most often found on the buttocks and posterolateral thighs of the majority of postpubertal females. This article aims to review the background, potential pathophysiology, and potential treatment options for cellulite, highlighting subcision as an ideal therapeutic option for this cosmetically distressing condition. Keywords: gynoid lipodystrophy, fibrous septae, radiofrequency, vacuum-assisted subscision